Resiprositas Kebaktian Anak dan Orang Tua dalam Al-Qur'an: Kajian Tafsir Maudhu'i atas Konsep Al-Abrar - Lalu Muhammad Zainul Ihsan (Ar-Rasikhin : Jurnal Ilmu Al-Qur'an dan Tafsir, 2026)
Popular religious discourse has thus far focused discussions of birr al-walidain solely on the obligations of children, so that the relationship of devotion within the family tends to be understood as a one-way relationship, neglecting the responsibilities of parents toward their children. In fact, social data indicates that violence against children occurs most frequently within the family, while exegetical studies on the concept of al-abrar have not yet explicitly linked it to reciprocity in this obedience. This study aims to formulate a Qur’anic paradigm that positions the concept of al-abrar as a framework for reciprocal virtue between children and parents, while also mapping out the boundaries of their respective rights and obligations. This study employs a qualitative method in the form of library research using a thematic exegetical approach, collecting verses on “al-abrar”, “birr al-walidain”, and children’s rights, which are analyzed using content analysis techniques with reference to authoritative exegetical works such as Tafsir al-Misbah, Tafsir Bahr al-Madid, and Mafatih al-Ghaib by Fakhruddin al-Razi. The results of the study show that al-Razi explicitly links the term al-abrar to mutual devotion—toward both parents and children—and emphasizes that worldly prosperity can only be achieved if this devotion is reciprocated by both parties. These findings indicate that “disobedience” within the framework of the Qur’an can be committed by both children and parents.